Effectiveness of Positive Thinking Training in Academic Engagement and Social Happiness of Depressed Students - Reza Mashhadi; Mohamad-Hassan Ghanifar; Toktam Sadat Jafar Tabatabaei; Samaneh Sadat Jafar Tabatabaei (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: Depression as a common mental disorder can seriously damage the academic procedure and psychological state of the students. Accordingly, the present study was conducted to determine the effectiveness of positive thinking skills training in academic engagement and social happiness of depressed students. Methods: The present study was a quasi-experimental study with a pretest-posttest design and a control group. The statistical population of this study included all male high school students in Zahedan, ran, in the academic year 2020-21. Among them, 30 eligible individuals were selected by purposive sampling method and randomly divided into two groups of 15 (experimental and control). Both groups answered the Reeve & Tseng (2011) Academic Conflict Questionnaire and Zare & Aminpour (2011) Social Happiness Questionnaire. The experimental group received positive thinking training by Seligman et al. (2005) as a group in eight 90-min sessions over two months. On the other hand, the control group did not receive any training. Data were analyzed using SPSS software (version 24) and univariate analysis of covariance. Results: The results showed that positive thinking training led to increased academic engagement (P<0.01, F=26.262) and increased social happiness (P<0.01, F=71.399) in depressed students. Conclusion: The findings showed that positive thinking skills effectively improved the academic engagement and social happiness of depressed students. Therefore, the results indicate the need to use positive thinking skill training to improve the socio-educational psychological characteristics of depressed students.